The Impact of Corporate Responsibility and Institutional Ownership on Manufacturing Financial Performance with Enviromental Performance - Muhammad Verdy Efriansyah Nasution; Indah Oktari Wijayanti (Journal of Creative Power and Ambition (JCPA), 2026)
Financial Performance represents the achievement of an entity's overall operational activities measured through financial indicators within a specific period. This research examines the financial performance fluctuations within the Indonesian manufacturing sector during the 2021–2024 post-pandemic recovery period. The purpose of this study is to evaluate the impact of the Community Donation Ratio (CDR), Corporate Social Responsibility (CSR), and Institutional Ownership on Financial Performance (FP), utilizing Environmental Performance (EP) as a mediating variable. Employing a quantitative approach and purposive sampling, the study analyzed 52 observations from manufacturing companies listed on the Indonesia Stock Exchange. Data were processed using multiple linear regression and classical assumption tests. The results indicate that CSR disclosure and EP significantly enhance corporate financial performance. Conversely, CDR and Institutional Ownership do not provide a significant positive contribution, with social donations even exerting negative pressure on profitability in combined models. Furthermore, while EP directly affects profitability, it is not proven to mediate the influence of CDR or Institutional Ownership on financial outcomes. The study concludes that high environmental standards and transparent social reporting are critical strategic drivers for economic stability and public trust in Indonesia's manufacturing industry.